1991
DOI: 10.1002/ana.410290413
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous electrical stimulation of corticospinal pathways at the level of the pyramidal decussation in humans

Abstract: Stimulation over the base of the skull can activate descending motor pathways to produce electromyographic (EMG) responses in muscles of the arm and leg. The evoked EMG responses were larger when the muscles were preactivated by a small voluntary contraction compared to when they were completely relaxed. The latency of these responses in preactivated muscles was approximately midway between that produced by electrical stimulation over the motor cortex, and by electrical stimulation over the cervical enlargemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
198
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(202 citation statements)
references
References 6 publications
3
198
1
Order By: Relevance
“…We also showed that the latency of MEP to the second pulse of double BST is the same as that to single BST in each healthy subject. Previous studies (Ugawa et al 1991(Ugawa et al , 1994 reported that the MEP latency to single BST was the same in both the active and the relaxed conditions because BST induces a single descending volley, irrespective of the state of muscle activation. For double BST, the MEP latency from the time of second BST is identical to the MEP latency to single BST.…”
Section: Mechanism Of Mep Enlargementmentioning
confidence: 85%
See 4 more Smart Citations
“…We also showed that the latency of MEP to the second pulse of double BST is the same as that to single BST in each healthy subject. Previous studies (Ugawa et al 1991(Ugawa et al , 1994 reported that the MEP latency to single BST was the same in both the active and the relaxed conditions because BST induces a single descending volley, irrespective of the state of muscle activation. For double BST, the MEP latency from the time of second BST is identical to the MEP latency to single BST.…”
Section: Mechanism Of Mep Enlargementmentioning
confidence: 85%
“…For double BST, the MEP latency from the time of second BST is identical to the MEP latency to single BST. The identical latencies are explainable by a single descending volley induced by either type of BST (Ugawa et al 1994). Therefore double BSTs in the relaxed condition are applicable to clinical practice by comparing them with normal values of MEP latency to single BSTs.…”
Section: Mechanism Of Mep Enlargementmentioning
confidence: 95%
See 3 more Smart Citations